INNOVATIVE CHARACTERISTICS OF THE FACTOR OF RELIGIOUS VALUES IN IMPLEMENTING THE CONCEPT "FROM NATIONAL RECOVERY TO NATIONAL PROGRESS" (Scientific journal of the Fergana State University, 2024)
The article examines the meaning of the concept “From National Revival to National Growth”, the organizational, social and spiritual foundations of its implementation, modern innovative features of the use of religion and religious values in this process.